State and problems of development of environmental accounting: experience of Kazakhstan - F. K. Yerdavletova; M. D. Zhumabayeva; N. S. Nurkasheva (Экономика: стратегия и практика, 2020)
The article is dedicated to a comprehensive study of the development of the theory and methodology of environmental accounting. As a research task, the authors determined an attempt to assess the state of development of environmental accounting in the Republic of Kazakhstan.Based on the analysis of various interpretations, the concept of environmental accounting is considered: the principal points are highlighted and a definition is given. In the course of research, such general scientific methods were used as observation, comparison, description, system and analytical approach, theoretical generalization, comparative study, scientific abstraction, expert assessment, effect-cause analysis.The authors have formulated a proposal on the classification of environmental costs, taking into account the environmental safety of companies and the results of environmental activities. The benefits and opportunities arising by implementation of environmental accounting systems are unveiled. The main directions forming the content-related side of environmental accounting are specified, namely: environmental cost accounting and environmental liability accounting.The results of the study can be applied in practice by managers, accountants, accounting analysts. The practical use of the research results can greatly contribute to a more reliable determination of the effectiveness and efficiency of environmental activities of companies.Established that environmental accounting forms a part of traditional accounting and should use all its concepts and principles. The results of environmental accounting should be reflected in the financial statements. The problems of development of environmental accounting are outlined: lack of statutory acts; the difficulty of evaluation of environmental liabilities; disordered environmental cost accounting, the groundlessness of attribution of these costs, etc.